Factors Controlling Vase Life of Waxflowers (Chamelaucium Desf. Varieties and Hybrids) - Cao, Dinh Dung (Curtin University, 2013)
Factors affecting vase life of Chamelaucium Desf. hybrids and hybrids between Chamelaucium and Verticordia Desf. were studied. Both genotype and cultivar determined the length of vase life of waxflowers. The use of sucrose or other sugar types and concentrations supplemented with 8-hydroxyquniline sulphate and/or silver thiosulphate extended the vase life of waxflowers cultivars depending on genotype. Flowers strongly competed with leaves for carbohydrates and water, affecting the vase life of waxflowers cultivars.